2005
DOI: 10.1037/0022-3514.88.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status, Resources, Psychological Experiences, and Emotional Responses: A Test of the Reserve Capacity Model.

Abstract: The current study used ecological momentary assessment to test several tenets of the reserve capacity model (L.C. Gallo & K. A. Matthews, 2003). Women (N = 108) with varying socioeconomic status (SES) monitored positive and negative psychosocial experiences and emotions across 2 days. Measures of intrapsychic and social resources were aggregated to represent the reserve capacity available to manage stress. Lower SES was associated with less perceived control and positive affect and more social strain. Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
225
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(251 citation statements)
references
References 93 publications
(142 reference statements)
22
225
1
3
Order By: Relevance
“…Possible reasons for this include more health-related knowledge, access to better jobs, access to health care, and thus, presumably (and evidently), less daily stress. 40,41 Compared with results from a health risk assessment questionnaire conducted in 2117 households in Western New York in 1999, this free clinic population has higher rates of obesity and medically diagnosed hypertension, asthma, diabetes, anxiety, and depression. 42 The high level of obesity in this population is probably related to the high level of diabetes and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for this include more health-related knowledge, access to better jobs, access to health care, and thus, presumably (and evidently), less daily stress. 40,41 Compared with results from a health risk assessment questionnaire conducted in 2117 households in Western New York in 1999, this free clinic population has higher rates of obesity and medically diagnosed hypertension, asthma, diabetes, anxiety, and depression. 42 The high level of obesity in this population is probably related to the high level of diabetes and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, other psychosocial resources (such as social support) have received substantial empirical scrutiny and also need to be accounted for in this process. In a daily study of workplace experiences, Gallo et al (2005) found lower levels of perceived appraisal, belonging, and tangible social support in lower SES groups, which were directly related to less positive and more negative affect. Low-SES individuals also suffer most with respect to social resources following major natural disasters (Kaniasty & Norris, 1995;Norris & Kaniasty, 1996).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Empirical evidence supports this model. In a daily study, Gallo et al (2005) found that lower SES women had fewer psychological resources available to them (including personal control) that were directly connected to more stressful daily experiences at work and home.…”
Section: Relating Initial Personal Control To Future Perceptions Of Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal caregivers with low income and poor job tend to have less self-control and thereby becoming highly sensitive to environmental stressors. They also tend to develop a form of physical and mental illness or a lower sense of well-being (Gallo, Bogart, Vranceanu, & Matthews, 2005).…”
Section: Introductionmentioning
confidence: 99%